2021
DOI: 10.3390/cancers13092236
|View full text |Cite
|
Sign up to set email alerts
|

Metronomic Chemotherapy

Abstract: Metronomic chemotherapy treatment (mCHT) refers to the chronic administration of low doses chemotherapy that can sustain prolonged, and active plasma levels of drugs, producing favorable tolerability and it is a new promising therapeutic approach in solid and in hematologic tumors. mCHT has not only a direct effect on tumor cells, but also an action on cell microenvironment, by inhibiting tumor angiogenesis, or promoting immune response and for these reasons can be considered a multi-target therapy itself. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(67 citation statements)
references
References 130 publications
0
67
0
Order By: Relevance
“…As continuous drug injection is clinically impossible owing to the very harmful side effects on normal cells, it is necessary to assess the efficacy of MTD, LDC, and CS methods comparatively. Despite promising preliminary results showed in different studies, only limited data has been available for a long time regarding the right dose of the different drugs to be used in the metronomic administration 44 . In many ways, development in MC and CS allows for the utilization of computational oncology at the bedside, since the optimization of an MC or CS regimen is largely achievable only with the help of modeling before clinical trials 16 , 45 .…”
Section: Discussionmentioning
confidence: 99%
“…As continuous drug injection is clinically impossible owing to the very harmful side effects on normal cells, it is necessary to assess the efficacy of MTD, LDC, and CS methods comparatively. Despite promising preliminary results showed in different studies, only limited data has been available for a long time regarding the right dose of the different drugs to be used in the metronomic administration 44 . In many ways, development in MC and CS allows for the utilization of computational oncology at the bedside, since the optimization of an MC or CS regimen is largely achievable only with the help of modeling before clinical trials 16 , 45 .…”
Section: Discussionmentioning
confidence: 99%
“…IL-17 and its downstream factor, granulocyte colonystimulating factor (G-CSF), are the leading players of inflammation; it has been reported that a high level of IL-17 induces cells to produce a paracrine network that confers resistance to anti-VEGF therapy. Serum G-CSF levels in CRC patients are higher than those in healthy volunteers and are associated with the stage of tumor progression [154,155] .…”
Section: Resistance To Anti-angiogenic Therapymentioning
confidence: 99%
“…The concept of MC, and its therapeutic use, have been extensively reviewed [19][20][21][22][23]25] as regards the treatment of breast cancer [34,35], non-small-cell lung cancer (NSCLC) [36], and high-risk pediatric malignancies [37]. A systematic review on MC compiles the clinical experience in different cancers such as breast, castration-resistant prostate, ovarian, glial, renal, lung, gastrointestinal, hepatocellular, multiple myeloma, melanoma, and head and neck [38].…”
Section: Metronomic Chemotherapy: a Multimodal Therapymentioning
confidence: 99%
“…As such, understanding these complex and multifaceted interactions could help improve the selection of drug combinations and schedules and reduce resistance to anticancer drugs. MC has become a new treatment option [22] that can be applied to chemotherapy, radiotherapy, and biotherapy [23]. In this regard, nanotherapy offers smartly targeted nanoparticles with modifiable properties to target components of the tumor microenvironment and could therefore be a good addition to MC [24].…”
Section: Introductionmentioning
confidence: 99%